Mastering the Old Testament ; v. 15B - Hubbard, David Allan (Dallas, TX Word, 1991)
Contents : v. 15B : Ecclesiastes, Song of Solomon. Includes bibliographical references.
Keywords: Bible O.T. Ecclesiastes -- commentaries; Bible O.T. Song of Solomon -- commentaries